62.6k views
2 votes
7(x-2)+3(x+2)=5(x-6)
Help

User Nagham
by
4.6k points

1 Answer

3 votes

Answer:

x = -4.4

Explanation:

We presume you want to solve for x.

Use the distributive property to eliminate parentheses.

7(x-2)+3(x+2) = 5(x-6)

7x -14 +3x +6 = 5x -30

Subtract the right side

(7x +3x -5x) +(-14 +6 +30) = 0

5x +22 = 0

Divide by 5

x + 4.4 = 0

Subtract the constant

x = -4.4

_____

Check

7(-4.4-2) +3(-4.4+2) = 5(-4.4-6) . . . . substitute -4.4 for x in the equation

7(-6.4) +3(-2.4) = 5(-10.4) . . . . . . . . . simplify

-44.8 -7.2 = -52 . . . . . true

User Mateen Kiani
by
5.0k points